2023
DOI: 10.1002/admt.202300095
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber‐Based Smart Plantar Pressure Mapping Insole System for Remote Gait Analysis and Motion Identification

Abstract: Traditional approaches for monitoring human gait have severe spatial and temporal restrictions with complex analysis methods and high cost, which are powerless to promote the development of intelligent life involving fitness, sport training, and healthcare. Herein, a portable smart insole system with high spatial resolution and simple manufacturing process to measure plantar pressure distribution anytime, anywhere for gait analysis is proposed. An insole‐shaped array of 104 piezoresistive sensors with highly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This review identified several types of technology integrated into the proposed measurement systems, including resistive technology [ 44 , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ], piezoelectric [ 39 , 40 , 46 ], capacitive [ 41 , 52 , 66 ], inductive [ 49 , 51 ], fiber optics [ 38 , 50 , [67] , [68] , [69] , [70] , [71] , [72] ] and textile technology with piezoresistive features [ [73] , [74] , [75] ]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review identified several types of technology integrated into the proposed measurement systems, including resistive technology [ 44 , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ], piezoelectric [ 39 , 40 , 46 ], capacitive [ 41 , 52 , 66 ], inductive [ 49 , 51 ], fiber optics [ 38 , 50 , [67] , [68] , [69] , [70] , [71] , [72] ] and textile technology with piezoresistive features [ [73] , [74] , [75] ]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of these sensors is well known and exhibits an almost linear and predictable response within a certain range of pressure values and operating temperatures [ 26 , 30 , [76] , [77] , [78] ]. The resistive sensors used are mostly force-sensing resistors (FSRs) [ 61 , 62 ], although other applications use Velostat, a polymeric film that follows the same behaviour as this type of sensor [ [63] , [64] , [65] ]; piezoresistive sensors: like resistive sensors, the entire body of these sensor is typically made of piezoresistive material. They are designed to react when the material is stretched, resulting in a variation in electrical resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gait analysis and recognition systems can play an important role in sports training. By conducting real-time gait analysis and status monitoring on athletes, coaches and athletes can better understand their physical condition, adjust training intensity and methods in a timely manner, and minimize the occurrence of sports injuries [7]. The system also has personalized functions that can be adjusted and optimized according to the characteristics and needs of each athlete, providing more accurate and personalized training guidance [8].…”
Section: Introductionmentioning
confidence: 99%
“…In practical applications, reconstruction operations based on raster formulas need to consider the horizontal and vertical transformations of two-dimensional image arrays. The horizontal transformation of an image array can be represented by formula (6), while the vertical transformation can be represented by formula (7). These transformations can be used to analyze the stripes obtained from the hologram, thereby restoring the shape and position information of the object.…”
mentioning
confidence: 99%